2005
DOI: 10.1111/j.1478-3231.2005.01159.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C‐associated autoimmunity in patients coinfected with HIV

Abstract: HIV coinfection appears to differentially modulate the frequency of HCV-related autoimmunity. However, autoimmunity is rarely accompanied by clinical manifestations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
1
8
0
1
Order By: Relevance
“…A recent retrospective analysis of the United Network for Organ Sharing (UNOS) database showed that although the 2 year survival of HIV patients (n = 138) was inferior to HIV -ve patients (70% vs 81%), the survival was similar in HIV -ve patients and HIV +ve patients without HCV or HBV co-infection [89] . Similar poor outcome in HIV patients with concomitant HCV infection has been observed in other studies [88,[90][91][92][93][94][95] . Survival of co-infected patients was inferior to HCV mono-infected patients at 1 year, 3 years, and 5 years (68%-80% vs 76%-87%, 56%-57% vs 72%-81%, and 33%-51% vs 72%-81%, respectively) [88,93,94] .…”
Section: Management Of Hiv-hcv Co-infected Patients With Endstage LIVsupporting
confidence: 68%
“…A recent retrospective analysis of the United Network for Organ Sharing (UNOS) database showed that although the 2 year survival of HIV patients (n = 138) was inferior to HIV -ve patients (70% vs 81%), the survival was similar in HIV -ve patients and HIV +ve patients without HCV or HBV co-infection [89] . Similar poor outcome in HIV patients with concomitant HCV infection has been observed in other studies [88,[90][91][92][93][94][95] . Survival of co-infected patients was inferior to HCV mono-infected patients at 1 year, 3 years, and 5 years (68%-80% vs 76%-87%, 56%-57% vs 72%-81%, and 33%-51% vs 72%-81%, respectively) [88,93,94] .…”
Section: Management Of Hiv-hcv Co-infected Patients With Endstage LIVsupporting
confidence: 68%
“…Only one recent study has compared cryoglobulinaemic features in patients with HCV-HIV and those with HCV infection alone. Woitas et al [22] studied 98 coinfected patients and 78 patients with HCV infection alone and found that coinfected patients had a lower frequency of cryoglobulinaemia, higher levels of cryocrit and positive RF. This low cryoglobulinaemic expression in HCV-HIV coinfected patients with respect to those with HCV infection alone suggests that HIV may attenuate the symptomatic expression of cryoglobulinaemia in patients with chronic HCV infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is not entirely clear whether HIV infection itself can trigger an autoimmune phenomenon and associated autoimmune hepatitis, but in some HIV/HCV co‐infected patients, the features of an autoimmune‐like hepatitis can be seen. It has been shown recently that HIV may differentially modulate HCV‐associated autoimmunity, as manifested by the presence and frequency of various auto‐antibodies (thyroglobulin, cardiolipin, for example), but it appears that, even in the presence of auto‐antibodies, the manifestations of autoimmunity are not clinically significant (44).…”
Section: Histopathologic Findings In Hiv/hcv Co‐infectionmentioning
confidence: 99%